System Thinking in Managing Technological Innovation Systems in Manufacturing Companies - Timothy O. Oyebisi; Abiodun S. Momodu; Segun O. Olabode (Naše gospodarstvo/Our economy, 2013)
This paper discusses models for managing Technological Innovation System (TIS) in a manufacturing setting. It reviews the existing six models for managing TIS: Tech- nology Push, Market Pull, Coupling Innovation Process (CIP), Functional Integration Innovation Process (FIIP), System Integration and Networking Innovation Process, and System of Innovation models. Major drawbacks of the model for managing TIS in manufacturing settings were identified. System thinking approach was then pro- posed as a suitable alternative for addressing these drawbacks. The basic principle of system dynamics on which system thinking is hinged is used to explain the propo- sed model. However, understanding and using this model are premised on the avai- lability of knowledge and skills in computer modeling and simulation software (e.g., Ithink, Vensim, and Powersim).